In vivo investigation of the multi‐exponential T2 decay in human white matter at 7 T: Implications for myelin water imaging at UHF. (28th October 2020) - Wiggermann, Vanessa; MacKay, Alexander L.; Rauscher, Alexander; Helms, Gunther
Abstract : Introduction: Multi‐component T 2 mapping using a gradient‐ and spin‐echo (GraSE) acquisition has become standard for myelin water imaging at 3 T. Higher magnetic field strengths promise signal‐to‐noise ratio benefits but face specific absorption rate limits and shortened T 2 times. This study investigates compartmental T 2 times in vivo and addresses advantages and challenges of multi‐component T 2 mapping at 7 T. Methods: We acquired 3D multi‐echo GraSE data in seven healthy adults at 7 T, with three subjects also scanned at 3 T. Stimulated echoes arising from B 1 + inhomogeneities were accounted for by the extended phase graph (EPG) algorithm. We used the computed T 2 distributions to determine T 2 times that identify different water pools and assessed signal‐to‐noise and fit‐to‐noise characteristics of the signal estimation. We compared short T 2 fractions and T 2 properties of the intermediate water pool at 3 T and 7 T. Results: Flip angle mapping confirmed that EPG accurately determined the larger B 1 + inhomogeneity at 7 T. Multi‐component T 2 analysis demonstrated shortened T 2 times at 7 T compared with 3 T. Fit‐to‐noise and signal‐to‐noise ratios were improved at 7 T but depended on B 1 + homogeneity. Adjusting the shortest T 2 to 8 ms and the T 2 threshold that separates different water compartments to 20 ms yielded short T 2 fractions at 7 T that conformed to 3 T data. Short T 2 fractions in myelin‐rich white matter regions were lower at 7 T than at 3 T, and higher in iron‐rich structures. Discussion: Adjusting the T 2 compartment boundaries was required due to the shorter T 2 relaxation times at 7 T. Shorter echo spacing would better sample the fast decaying signal but would increase peripheral nerve stimulation. Multi‐channel transmission will improve T 2 measurements at 7 T. Conclusion: We used a multi‐echo 3D GraSE sequence to characterize the multi‐exponential T 2 decay at 7 T. We adapted T 2 parameters for evaluation of the short T 2 fraction. Obtained 7 T multi‐component T 2 maps were in good agreement with 3 T data. Abstract : Multi‐component T2 mapping for myelin water imaging (MWI) at 7T offers the promise of signal‐to‐noise ratio benefits, but faces the challenges of specific absorption rate (SAR) limits and shortening of T2 times. We demonstrated the feasibility of adapting a multi‐echo 3D‐GraSE sequence from 3T to 7T MRI and discussed the difficulties of increased B1 + inhomogeneity and other challenges at 7T for correct estimation of the short T2 signal fraction.